ChemInform Abstract: Photoinduced Ultrafast Heterogeneous Electron Transfer at Molecule‐Semiconductor Interfaces. Issue 1 (January 2015) - Nieto‐Pescador, Jesus; Abraham, Baxter; Gundlach, Lars
Abstract Review: 71 refs.